2013
DOI: 10.1002/ijc.28283
|View full text |Cite
|
Sign up to set email alerts
|

HPV self-sampling or the Pap-smear: A randomized study among cervical screening nonattenders from lower socioeconomic groups in France

Abstract: 5 ECCA (European cervical cancer association) Brussels, Belgium Today in France, low attendance to cervical screening by Papanicolaou cytology (Pap-smear) is a major contributor to the 3,000 new cervical cancer cases and 1,000 deaths that occur from this disease every year. Nonattenders are mostly from lower socioeconomic groups and testing of self-obtained samples for high-risk Human Papilloma virus (HPV) types has been proposed as a method to increase screening participation in these groups. In 2011, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 22 publications
8
110
1
Order By: Relevance
“…Because it is known that under-screened women are at increased risk of cervical cancer, targeting non-attendees of the screening program could improve the effectiveness of cervical screening [31, 32]. Non-attendees are mostly from lower socioeconomic groups and self-testing has shown to facilitate access to cervical screening for women in low-resource areas [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because it is known that under-screened women are at increased risk of cervical cancer, targeting non-attendees of the screening program could improve the effectiveness of cervical screening [31, 32]. Non-attendees are mostly from lower socioeconomic groups and self-testing has shown to facilitate access to cervical screening for women in low-resource areas [32].…”
Section: Discussionmentioning
confidence: 99%
“…In countries with publicly funded cervical cancer screening programs, irregular attendance or non-attendance to screening is one of the key barriers to further reducing cervical cancer rates 19,20 . Lower screening rates have been reported in specific populations, such as immigrant women, women of low socio-economic status, and Indigenous women 21,22 .…”
Section: Using Hpv Self-collection To Reach Under-screened Womenmentioning
confidence: 99%
“…Self-sampling is a method to collect cervical specimen by using a special designated device to collect cervical cells at squamouscolumnar junction by the user themselves without assistance of medical personnel. Studies have shown that using self-sampling method increases participation of non-responders in screening programs (Bosgraaf et al, 2014a;Piana et al, 2011;Sancho-Garnier et al, 2013). Self-sampling samples have also been shown to be suitable for HPV testing (Sancho-Garnier et al, 2013;Scarinci et al, 2013;Tamalet et al, 2013;Othman and Othman, 2014) even in a in a large-scale (Harper et al, 1999).…”
Section: Self-collection Tools For Routine Cervical Cancer Screening:mentioning
confidence: 99%
“…The use of self-sampling may lead to higher acceptability to screening (Gok et al, 2012a;Wikstrom et al, 2011). Self-sampling is more attractive for the non-attendees in countries which have organized screening and from rural women in countries which have limited resources (Sancho-Garnier et al, 2013). It can be an alternative method to women who are reluctant to undergo pelvic examination due to shyness (Scarinci et al, 2013) or too busy looking after the family which is often the case amongst Asian women (Othman and Rebolj, 2009).…”
Section: Advantages and Limitations Of Self-samplingmentioning
confidence: 99%